Electroacupuncture-Assisted Craniotomy on an Awake Patient - Sidhu, A.; Murgahayah, T.; Narayanan, V.; Chandran, H.; Waran, V. (Elsevier, 2017)
Although acupuncture has existed for over 2000 years, its application as an anesthetic aid began in the 1950s in China. The first surgical procedure performed under acupuncture anesthesia was a tonsillectomy. Soon thereafter, major and minor surgical procedures took place with electroacupuncture alone providing the anesthesia. The procedures performed were diverse, ranging from cardiothoracic surgery to dental extractions. Usage of acupuncture anesthesia, specifically in neurosurgery, has been well documented in hospitals across China, especially in Beijing, dating back to the 1970s. We present a case of a 65-year-old man who presented with right-sided body weakness. He had a past medical history of uncontrolled diabetes mellitus, hypertension, and obstructive sleep apnea requiring use of a nasal continuous positive airway pressure device during sleep. We performed a computed tomography brain scan, which revealed a left-sided acute on chronic subdural hemorrhage. Due to his multiple comorbidities, we decided to perform the surgical procedure under electroacupuncture anesthesia. The aim of this case report is to describe a craniotomy performed under electroacupuncture on an elderly patient with multiple comorbidities who was awake during the procedure and in whom this procedure, if it had been performed under general anesthesia, would have carried high risk.